Pengaruh Financial Distress, Financial Literacy, dan Lifestyle Terhadap Keputusan Penggunaan Paylater Pada Mahasiswa Akuntansi - Sabrina, Nadia Putri; Trisnaningsih, Sri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The development of fintech has led to many developments in payment services, including Paylater, which has gained popularity among the masses, particularly among generation Z. The objective of this study is to investigate the factors that affect the use of Paylater, which include Financial Distress, Financial Literacy, and Lifestyle in college students. The selection of college students was done because they belong to the young generation that utilizes many financial services through technology, and at the same time is subject to pressure from both the economy and consumption practices owing to technological advancements and future trends. In this study, the methodology used was SEM-PLS analysis method through the use of SmartPLS software version 4.0. This study gathered data by administering an online survey using Google Forms among 91 students from the Accounting Study Program in the 2022–2023 intake from UPN “Veteran” East Java. Based on the findings, this study concludes that Financial Distress, Financial Literacy, and Lifestyle have a significant positive effect on the intention to adopt Paylater among Accounting Students in the 2022–2023 intake from UPN “Veteran” East Java with the financial distress variable having a significance value of 0.042 <0.05 with a coefficient value of 0.180, the financial literacy variable having a significance value of 0.000 <0.05 with a coefficient value of 0.501, and the lifestyle variable having a significance value of 0.037 <0.05 with a coefficient value of 0.197.